Catalytic Oxidative Degradation of Hydrocarbons Using Novel Metal-Free Nanocarbon Catalysts - Duan, Xiaoguang (Curtin University, 2015)
This research presents novel nanocarbon materials as green and metal-free carbocatalysts for advanced oxidative processes toward environmental remediation. Various nanocarbons exhibit high catalytic activity in activation of sulfate oxidants for degradation of water contaminants. The tailored surface chemistry of nanocarbons and insightful mechanistic studies for catalytic activation of superoxides were revealed via deliberate materials design, advanced characterization techniques and theoretical calculations.The findings would significantly contribute to materials chemistry, environmental science, carbocatalysis and other related fields.